2023
DOI: 10.1088/2043-6262/acd8b6
|View full text |Cite
|
Sign up to set email alerts
|

Structural, spectroscopic and morphology studies on green synthesized ZnO nanoparticles

Abstract: Zinc oxide nanoparticles (ZnO NPs) were synthesised using Tabernaemontana divaricata flower extract (TFE) in different weight percentages by facile, eco-friendly and cost-effective green synthesis method. Formation and structure of the ZnO NPs were studied by powder XRD, FT−IR, Raman and TEM studies. The crystals formed are of hexagonal wurtzite structure with biological functional groups attached. Average crystallite size of the ZnO NPs (17.5−23.3 nm) was obtained from the analysis of powder XRD data which in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…[ 10 ] In contrast, surface modification of the conducting grains by poorly conducting extract molecules, i.e., modification of the grain boundary surfaces will change the dielectric constant of the modified ZnO NPs which depends on the polarizable bonds on the surface manifested through their shape and size. [ 58 ] These may explain why the dielectric constant values at steady temperatures in the low‐frequency range change with the changing particle size as observed in the present case (at 50 Hz and 24 °C, ZnO0: εr$\left(\epsilon\right)_{r}$ = 1040, D = 17.5 nm; [ 71 ] ZnO10: εr$\left(\epsilon\right)_{r}$ = 55, D = 20.8 nm [ 71 ] )…”
Section: Resultsmentioning
confidence: 69%
See 4 more Smart Citations
“…[ 10 ] In contrast, surface modification of the conducting grains by poorly conducting extract molecules, i.e., modification of the grain boundary surfaces will change the dielectric constant of the modified ZnO NPs which depends on the polarizable bonds on the surface manifested through their shape and size. [ 58 ] These may explain why the dielectric constant values at steady temperatures in the low‐frequency range change with the changing particle size as observed in the present case (at 50 Hz and 24 °C, ZnO0: εr$\left(\epsilon\right)_{r}$ = 1040, D = 17.5 nm; [ 71 ] ZnO10: εr$\left(\epsilon\right)_{r}$ = 55, D = 20.8 nm [ 71 ] )…”
Section: Resultsmentioning
confidence: 69%
“…As porosity decreases when effective pressure on the material is increased and as samples were pelletized under high pressure for the dielectric measurements, the amount of void is naturally reduced in the pelletized samples while compared to that present in powdery as‐grown samples. From morphology study on these two samples reported earlier, [ 71 ] no apparent difference in the surface texture could be distinguished which may be due to small difference in the porosity levels in ZnO0 and ZnO10 samples.…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations